(3MQR GdCeGfi hhLg GdJgGfjs - (3GdbGSe Hf ajQg Hf Nda Hf CMeO GdQYjfj, CHh eMeO GdTGWHj,J (B590 (3g` s ((3CfSGf Hf jhSa Hf QSJe Gdbhfhi s)
(3ChdgG (B:s
(3HOCJ HHSe Gddg ai GdfXe ChdkG JHGQc QMeGfkG QMjekG heFdkG hHYO aLYd Gddg ajfG cJGHg aLGgO Hg MHd GdgOi eJMHdkG s
(3BNQgG (B:s
(3ajG NjQ ZaGQ hjG NjQ QGMe hjG NjQ eCehd LOi hJaVdG JeJ HMeO Gddg hMSf Jhajbg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B180 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B110s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B646s
Keywords: (3GdbQGAGJ hGdJLhjOs